Detonation wear-resistant coatings, alloy powders based on Cr-Si - Довгаль, А.Г.; Щепетов, В.В.; Гулевець, В.Д. (Proceedings of National Aviation University, 2009)
Coatings from composition material Cr-Si-B on steel by detonation spraying method are obtained. Composition, structure and tribotechnical characteristics of coatings in comparison with traditional materials on the basis of Ni-Cr and alloy of tungsten and cobalt are investigated.